Risk Assessment of Sudden Cardiac Death in Patients with Atrial Fibrillation Using CHA2DS2-VASc score - Shrestha, Manoj; Luitel, Bibek (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Probability of sudden cardiac death is more in patient with atrial fibrillation than those without this condition. CHA2DS2-VASc score can be useful to predict the likelihood of sudden cardiac death among the patients with atrial fibrillation. The current study aims to evaluate the diagnostic value of the CHA2DS2-VASC score in anticipating sudden cardiac death among admitted patients with atrial fibrillation. Methods The study was conducted for three months i.e. from 16th May 2023 till 17th August 2023. In this research 150 patients fulfilling inclusion criteria were taken. Patient details, ECG features and risk factors were evaluated. CHA2DS2-VASc score was determined and the findings were analyzed statistically. Results The study population constituted 60% males and 40% female with mean age of 58.9±10.99. The mean CHA2DS2-VASc score was 3.2±2.8. 25.3% of patients with atrial fibrillation had sudden cardiac death. For prediction of sudden cardiac death, CHA2DS2-VASc score had a sensitivity of 78.3%, specificity of 82.3%, positive predictive value of 59.1%, negative predictive value 92% and a diagnostic accuracy of 81.3% for predicting risk of sudden cardiac death. Conclusions The diagnostic accuracy of the CHA2DS2-VASc score was 81.3% among patients having atrial fibrillation for predicting sudden cardiac death, making it an effective predictor.